Subjective well being children with ADHD - Iriani Indri Hapsari; Aulia Iskandarsyah; Poeti Joefiani; Juke R Siregar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
Identifying how subjective well-being is based on the perceptions of children with ADHD itself and to find out what aspects show children with ADHD are feeling their well-being and what aspects show children with ADHD have not developed their well-being its important to be known. The child's voice is important and is the most accurate data in showing what the child feels themselves include about their subjective wellbeing. Case study qualitative research methods by interview with a sample of 44 children comprising 3 females, 41 males (age 8-12). Data analysis was using thematic analysis with NVIVO 12. The results indicate that children with ADHD in general, in their lives, are already having their well-being and some are not. In general the factors that make children with ADHD feel their well-being or not, include about capable do something, when get what they want, and have positive/ negative relationships with the people around them. It is important to pay attention to the subjective well-being children with ADHD, it is hoped that teachers, parents, and government can further optimize their respective roles and collaborate with each other to jointly pay attention to children's well-being with various strategies and policies.